Ear drops for the removal of ear wax - Burton, Martin J (Cochrane Database Syst Rev, 2018)
Review withdrawn from Issue 7, 2018. It has been superseded by the new review: Aaron K, Cooper TE, Warner L, Burton MJ. Ear drops for the removal of ear wax. Cochrane Database of Systematic Reviews 2018, Issue 7. Art. No.: CD012171. DOI: 10.1002/14651858.CD012171.pub2. The editorial group responsible for this previously published document have withdrawn it from publication.